Migration, labor mobility and household poverty in Nigeria: A gender analysis - Mistura Rufai; Adebayo Ogunniyi; Kabir Kayode Salman; Motunrayo Oyeyemi; Mutiat Salawu (Economies, 2019)
The increase in the geographical mobility of labour as a result of poverty, unemployment and unstable economic conditions, among other factors, especially among professionals, has been associated with a brain drain in Nigeria. Despite the high level of migration and subsequent remittances from migrants, a large proportion of Nigerians still live in poverty. The increased participation of women in migration in the country also brings to the fore the existence of gender-specific migration experiences and how this has in turn affected their households. Based on gender, this study assesses the extent of labour mobility, its determinants and how it influences remittance inflows and household poverty using the logit regression model Propensity Score Matching and Linear Regression with Endogenous Treatment Effect Approach. Results reveal that while more males travelled for employment purposes, more females travelled due to marriage arrangements. More of the migrants that were working after migration had worked before migration and had the highest average amount of remittance sent to households. The study shows that labour mobility increases the amount of remittance sent to households. However, the increase was higher among male migrants than female migrants. More than half of the migrants had poor households; meanwhile, labour mobility was found to reduce the extent of poverty. The study recommended that policies that improve the welfare of labour and reduce the brain drain, unemployment and closures of enterprises in the country should be put in place. Also, effective policies and interventions that promote the use of remittances to achieve maximum reductions in poverty should be pursued.
Keywords: 330; gender; labour movement; remittance; welfare